THE ROLE OF MOBILE APPS IN CREATING INTEGRATED SCIENCE LESSONS FOR 4TH GRADE - Uzogboev Khojiakbar Qabiljon Ugli (International Scientific and Current Research Conferences, 2023)
The article explores the impact of modern mobile technologies on the process of teaching natural sciences in elementary school. The author examines the problems associated with traditional teaching methods and suggests an innovative approach using mobile applications. The article analyzes how mobile technologies can be incorporated into the learning process to make lessons more interactive, accessible and exciting for 4th grade students. Specific examples of applications that contribute to the formation of integrated lessons in natural sciences are given, and the positive results of the introduction of such approaches into educational practice are also considered. The work calls for further research and application of mobile technologies in education in order to improve the effectiveness of teaching scientific subjects at the initial stage of education.